2008
DOI: 10.1007/s00415-008-0726-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specificities in Alzheimer's disease and mild cognitive impairment

Abstract: We interpret the results in light of a gender-specific cognitive reserve and conclude that the gender-specificity of neuropsychological performance needs to be accounted for in clinical diagnosis of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 39 publications
(56 reference statements)
4
40
1
1
Order By: Relevance
“…The finding that women did better than men on the Digit Symbol-Coding test is consistent with previous research showing that older women tend to do better on tasks of cognitive performance than do older men (Aartsen, Martin, Zimprich, & Longitudinal Aging Study, Amsterdam, 2004) and that the prevalence of mild cognitive impairment in people aged 71-89 years appears higher in men than in women (Petersen et al, 2010). Similarly, prior studies have found that women have better verbal memory than men (Aartsen et al, 2004;Gale, Baxter, Connor, Herring, & Comer, 2007;van Hooren et al, 2007), although there may not be sex differences in visual memory (Beinhoff, Tumani, Brettschneider, Bittner, & Riepe, 2008;Gale et al, 2007). Thus, while a sex difference in memory could have potentially affected performance on the Digit Symbol-Coding subtest in this age group, females tend to perform better on measures of processing (or perceptual) speed than males (Hedges & Nowell, 1995), and this sex difference was observed in the standardization sample for Digit-Symbol Coding (Irwing, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…The finding that women did better than men on the Digit Symbol-Coding test is consistent with previous research showing that older women tend to do better on tasks of cognitive performance than do older men (Aartsen, Martin, Zimprich, & Longitudinal Aging Study, Amsterdam, 2004) and that the prevalence of mild cognitive impairment in people aged 71-89 years appears higher in men than in women (Petersen et al, 2010). Similarly, prior studies have found that women have better verbal memory than men (Aartsen et al, 2004;Gale, Baxter, Connor, Herring, & Comer, 2007;van Hooren et al, 2007), although there may not be sex differences in visual memory (Beinhoff, Tumani, Brettschneider, Bittner, & Riepe, 2008;Gale et al, 2007). Thus, while a sex difference in memory could have potentially affected performance on the Digit Symbol-Coding subtest in this age group, females tend to perform better on measures of processing (or perceptual) speed than males (Hedges & Nowell, 1995), and this sex difference was observed in the standardization sample for Digit-Symbol Coding (Irwing, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the influence of sociodemographic factors, the fact that female gender predicts gains in memory corroborates previous findings that women profit more from CT programs especially in the memory domain, although [34] found effects for verbal, not figural memory which fit better to the hypothesis of a "gender-specific cognitive reserve" [68], which assumes larger plasticity in verbal episodic memory in women. Thus, our finding that gains in non-verbal long-term memory, attention and set-shifting was predicted by female gender needs further investigation.…”
Section: E Kalbe Et Al Healthsupporting
confidence: 85%
“…These results suggest a diminution of the female advantage but not an elimination. Others have also reported an elimination 28 or even a reversal 29 of the female advantage in verbal memory in AD dementia. Smaller HpVR were associated with poorer delayed recall performance and trended towards an association with immediate recall (p 5 0.10) among patients with AD dementia.…”
mentioning
confidence: 95%